Implementation of eMaintenance concept within the Swedish railway - Juntti, Ulla; Karim, Ramin; Larsson, Lillemor (Luleå tekniska universitet, Drift, underhåll och akustik, 2014)
An available, reliable and well-maintained railway is the foundation for competition and market growth. Demands on high standardsfor reliable rail transport, tight turnaround times and high utilization of resources (machines, workshops , staff) makes minimumdisturbance in the system to quickly disrupt the entire process of lost capacity, delays and reduced quality to customers as a result.The Swedish railway composed after deregulation, of several different parties, each one with individually objectives and strategy tomaintain their assets and rolling stock. Although some data are railway system common no greater sharing of operation andmaintenance data exists, which creates the risk of sub-optimisation.Luleå Railway Research Center (JVTC) has since 2005 determinedly conducted research in eMaintenance with the aim of usingdifferent types of condition data to develop decision support using preventive measures to prevent disruption of the railway systemin a cost effective manner. eMaintenance aims to perform and control the maintenance with help of condition data and isinterdisciplinary field based on the information and communication technology ( ICT) to ensure that maintenance is carried out inline with both the customer and the supplier's business goals and intrinsic components in all parts of a system's life cycle.eMaintenance concept has developed progressively over the years and now it is acdcepted o be implemented as a pilot project calledePilot119 in the north part of Sweden on track section 119 between Luleå and Boden. ePilot119 delivers a collaboration platform forthe development needs and requirements from various stakeholders to find solutions that enable and transform the Swedishfragmented rail industry to and an integrated system. ePilot 119 will demonstrate the advantages of working with informationtechnology and data in real time to control railway traffic and service. The approach is based on enhanced collaborationmethodology with a framework project and a central team that is unifying for finding ...